Presentation and Determination of Hop (Humulus lupulus L.) Cultivars by a Min-Max Model on Composition of Hop Essential Oil - Kač, Milica; Kovačevič, Miroslav (BrewingScience, 2000)
A min-max model of GC data on composition of hop essential oils for presentation and determination of different hop varieties developed on the Institute of Hop Research and Brewing in Žalec by Draga Kralj and coworkers was used to describe the essential oil composition of some commercially interesting German cultivars (Perle, Magnum, Taurus) and some typical modern Slovene cultivars (Celeia, Cerera). The cultivars in question were also compared to the so called European traditional aromatic hops: i.e. the aromatic hops of Bavarian and/or Czech origin together with English Fuggles and Goldings which are considered standard high quality aromatic accessions. The results are commented also for differences in essential oil composition owing to different growing areas. The matching between samples originating from different growing areas is very good: as expected, the composition of the essential oil for a given accession in a given growing area varies little from year to year, is slightly more different for the same accession grown in different growing areas but varies widely (i.e. is characteristically different) for different accessions. The 31-parameter model is a simple and reliable way for cultivar identification and determination. The matching of these parameters for each variety with the parameters for European traditional aromatic hops is also an objective indication of the organoleptically determined aroma score.